Analysis of Learning Difficulties About Introduction to Accounting And Finance of Worksheet Material Learning - Martodiryo, Suratno; Rizky, M.; Hadi, Rizali (The Islamic Education and Multiculturalism Foundation, 2023)
The results of the analysis test can be used as a means to know the students' learning difficulties and as a guide to know how to overcome such difficulties. The purpose of this study is to identify and know the causes of learning difficulties on accounting worksheet materials. In analyzing the data presented the difficulty of learning accounting work sheet material based on the cognitive domain. The results showed that students had difficulty working on the worksheet on the dimensions of remembering i.e :